Effect of bypass protein on yield and composition of milk in crossbred cows* - Kalbande, V H; Thomas, C T (The Indian Journal of Animal Sciences, 2012)
Jersey crossbred cows (18) were divided into 3 graups (1, 2 and 3) of 6 animals each as unifarmly as possible with regard to their body weights and milk production and maintained on 3 respective isonitrogenous and isocaloric concentrate mixtures A, Band C with varying rumen degradable pratein (RDP) to undegradable dietary protein (UDP) ratios of 37:63; 52:48 and 70:30 for 100 days starting fifth day pastpartum. The feed intake of animals was increased significantly (P<0.01) with increase in UDP levels in the concentrates mixtures, the percent dry matter intake calculated for the entire period of experiment, being 3.70, 3.38 and 3.14 for groups 1, 2 and 3 respectively. The data on fortnightly body weights of animals revealed that, while animals maintained on concentrate mixture A with UDP level of63.3 8% had a total gain of 10.38 kg (P<0.01) over a period of 100 days, those fed concentrate mixture B with UDP level of 47.55% and C with UDP level of 29.75%, lost their body weights to the extent of 3.33 and 5.83 kg, respectively, over the same period of experiment. Result on lactation studies revealed significant (P<0.01) differences in total milk yield between the groups fed on the 3 concentrate mixtures. A, Band C the average daily milk yield calculated over a 1 00-day-lactation period being 10.11, 7.18, and 6.32 kg respectively. Efficiency of milk production, though not significant, was also higher with higher levels of UDP over the entire period of experiment. An overall evaluation of results on milk production and feed conversion efficiency indicated that higher levels of UDP in concentrate mixture stimulated feed consumption, resulting in better availability of nutrients for higher milk production. Results of the studies also emphasize the need for formulating suitable feed combinations based on their UDP/by-pass protein levels in addition to total protein for optimum milk production and milk composition.